KIOS PASAR SEBAGAI OBJEK JAMINAN KREDIT - Nurul Masfufah (Arena Hukum, 2016)
AbstractThis journal aims to identify and analyze the market stalls as the object of credit guarantees. This research is a normative juridical research (Normative Legal Research) by using the conceptual legislation approach, assisted with legal materials that will be described, and analyzed in relation to one another. Guarantee intimately is related to loans. Good guarantee should be able to provide a sense of security, provide legal certainty and to provide legal protection for creditors. There are various forms of guarantees given debtors, including in the form of a market stall. Market stall in law collateral material can not be categorized as immovable, for to be categorized as